2022
DOI: 10.1002/jev2.12271
|View full text |Cite
|
Sign up to set email alerts
|

The dark side of foetal bovine serum in extracellular vesicle studies

Abstract: Extracellular vesicles (EVs) have been shown to be involved in cell‐cell communication and to take part in both physiological and pathological processes. Thanks to their exclusive cargo, which includes proteins, lipids, and nucleic acids from the originating cells, they are gaining interest as potential biomarkers of disease. In recent years, their appealing features have been fascinating researchers from all over the world, thus increasing the number of in vitro studies focused on EV release, content, and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 203 publications
(336 reference statements)
1
31
0
Order By: Relevance
“…Upon addition of cells and media, microchannels were placed on a rocking base of a WAVE bioreactor (Xuri Cell Expansion System W5, GE Healthcare) in a standard humidified incubator (37 °C, 5% CO 2 ) at a rocking angle of 8° and rocking speed of 20 rocks/minute for 72 h [ 17 ]. For static aggregates, 15,000 and 50,000 cells were seeded in each well in 200 µL of culture medium in an ultra-low attachment (ULA) 96-well plate with a round bottom (Corning, Corning, NY, USA) for 72 h. For the EV isolation experiments, aggregates were pooled together in EV depleted culture media (i.e., the growth medium containing EV-depleted FBS through ultracentrifugation [ 37 ]) and transferred to ULA 6-well plates into three wells each containing 2 mL of EV-depleted media. Dynamic aggregates were placed on the WAVE bioreactor at a rocking angle of 8° and rocking speed of 20 rocks/minute for 72 h.…”
Section: Methodsmentioning
confidence: 99%
“…Upon addition of cells and media, microchannels were placed on a rocking base of a WAVE bioreactor (Xuri Cell Expansion System W5, GE Healthcare) in a standard humidified incubator (37 °C, 5% CO 2 ) at a rocking angle of 8° and rocking speed of 20 rocks/minute for 72 h [ 17 ]. For static aggregates, 15,000 and 50,000 cells were seeded in each well in 200 µL of culture medium in an ultra-low attachment (ULA) 96-well plate with a round bottom (Corning, Corning, NY, USA) for 72 h. For the EV isolation experiments, aggregates were pooled together in EV depleted culture media (i.e., the growth medium containing EV-depleted FBS through ultracentrifugation [ 37 ]) and transferred to ULA 6-well plates into three wells each containing 2 mL of EV-depleted media. Dynamic aggregates were placed on the WAVE bioreactor at a rocking angle of 8° and rocking speed of 20 rocks/minute for 72 h.…”
Section: Methodsmentioning
confidence: 99%
“…Fetal bovine serum (FBS) is a common supplement for cell culture media that contaminates sEV samples with exogenous EVs and other particles, such as lipoproteins or protein complexes [ 15 , 17 , 18 ]. As an alternative, it is suggested that EV-depleted FBS be used.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, it is suggested that EV-depleted FBS be used. However, depletion protocols cannot remove EVs completely and the resulting FBS is not EV-free [ 17 , 18 , 26 , 27 ]. Another alternative solution is the usage of serum-free medium, but it may induce cellular stress and cause changes in the cellular phenotype, EV cargo packaging and release mechanisms [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have recently shown that exogenous EVs from serum supplements can have significant effects on experimental outcomes [3][4][5][6][7][8][9]. These findings have encouraged the development of mitigation strategies such as the author/funder.…”
Section: Introductionmentioning
confidence: 99%